2020
DOI: 10.1007/s11270-020-04710-y
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Microplastics in Water, Sediment, and Milkfish (Chanos chanos) at the Downstream Area of Citarum River, Indonesia

Abstract: Citarum River is the largest natural stream in West Java, Indonesia, flowing across an area of 6614 km 2 . About 3000 industries discharge their wastewater into the stream, affecting almost 19 million people who live along the river. Considering the perseverance and the prospective toxicity of microplastics (MPs), investigating their concentrations in this river is critical to help illustrate the exposure of the risks to the residents of the area and beyond. This study was focused on identifying the MPs concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
15
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 47 publications
5
15
2
6
Order By: Relevance
“…A recent study byYin et al (2020) also reported bres as a dominant type of MPs with 41-49 to 100 % of the total types of MPs. The same highest proportions of bres documented bySembiring et al (2020). In another study,Zhang et al (2019) detected the bres in sediments to be 60%, with fragments being 30%.…”
supporting
confidence: 52%
“…A recent study byYin et al (2020) also reported bres as a dominant type of MPs with 41-49 to 100 % of the total types of MPs. The same highest proportions of bres documented bySembiring et al (2020). In another study,Zhang et al (2019) detected the bres in sediments to be 60%, with fragments being 30%.…”
supporting
confidence: 52%
“…Semenjak saat itu, mulai banyak penelitian mikroplastik di Indonesia seperti di Teluk Jakarta (Manalu dkk. 2017), Kabupaten Bandung (Alam dkk., 2019), Laut Kupang (Hiwari dkk., 2019), Teluk Benoa Bali (Nugroho dkk., 2018), Surabaya (Firdaus dkk., 2019), hingga yang terakhir di Sungai Citarum (Sembiring & Fareza, 2020).…”
Section: Pendahuluanunclassified
“…Selain itu, tingkat konsentrasi penduduk yang tinggi di pulau Jawa dibandingkan di pulau lain, membuat penelitian mikroplastik pada lingkungan yang dikaitkan dengan faktor antropogenik menjadi lebih relevan dan menarik dilakukan. Terlihat dari dominasi penelitian mikroplastik di Pulau Jawa yang banyak mengangkat isu badan air yang tercemar (Ramadan & Sembiring, 2020;Sembiring & Fareza, 2020), potensi mikroplastik dari pencemaran udara (Asrin & Dipareza, 2019;Syafei dkk., 2019;Yudison, 2020), ataupun potensi pencemaran akibat dari daerah padat penduduk (Afdal dkk., 2019). Meskipun begitu, dengan masih sedikitnya penelitian mikroplastik di pulau lain, menjadi tantangan untuk diteliti lebih dalam.…”
unclassified
“…However, there is no correlation between microplastic concentration in water and sediment with a microplastic concentration in milkfish. However, the presence of microplastics in each sample originating from various points in the sampling area should be noted for both local government and residents [19].…”
Section: Microplastics At Citarum Watershedmentioning
confidence: 99%
“…Sample Locations in The Citarum Watershed (A) Ciwalengke River (B) Jatiluhur Reservoir (C) Muara Gembong[17][18][19] …”
mentioning
confidence: 99%